Negotiating adolescence in times of social change (Cambridge University Press, 2000)
The decline of the socialist governments in Eastern and Central Europe and the resulting political and economic reorganizations of the 1990s provided a dramatic illustration of the far-reaching effects of social change. For those interested in the health and well-being of youth, such instances of social upheaval raise the question of how young people are affected socially and psychologically by societal changes, and whether their development is compromised or enhanced. This important volume considers the processes through which societal changes exert an impact on the course of adolescent development and identify individual and contextual factors that can modify the impact of social change and enhance the likelihood of a successful transition to adulthood.